Bridging the Gap Between Aging Research and Practice: A New Strategy for Enhancing the Consensus Workshop Model. (June 2020) - Trevino, Kelly M.; Canin, Beverly; Healy, Charlotte; Moran, Sheila; Trochim, William M.; Martin, Peter; Pillemer, Karl; Sirey, Jo Anne; Reid, M. Cary
Objectives: The Cornell Research-to-Practice (RTP) Consensus Workshop Model is a strategy for bridging the gap between aging research and practice but lacks a technique for evaluating the relative importance of ideas. This project assessed the feasibility of adding a quantitative survey to the RTP model to address this gap.Method: Older adults with cancer (OACs), OAC caregivers, researchers, clinicians, and advocacy organization representatives participated in a RTP workshop on implementing psychological interventions for OACs. Following an in-person workshop, participants completed surveys assessing the relative importance of barriers and strategies for psychological intervention implementation.Results: Seventeen of 35 participants completed the survey, the majority of which were likely clinicians. Barriers and strategies to implementation rated as having the greatest impact were associated with the care team and institutional factors.Conclusion: Quantitative ratings add novel information to the RTP model that could potentially enhance the model's impact on aging research and practice.